A Review of the second Carnegie Commission of enquiry into poverty in South Africa - Wilson, Francis (My University, 1985)
What follows is the barest outline of some of the major issues emerging from the Second Carnegie Inquiry into Poverty and Development. I intend to flesh out these bones in the seminar in the hope of provoking critical discussion. This seminar will focus on poverty and the processes of impoverishment in Southern Africa, and on the second Carnegie Inquiry, which has been going on over the past five years. Background, and introduction: Purpose of the Inquiry is not just to document poverty, but to engage in policy-oriented research: research to assist the society to develop strategies to move away from poverty.
African Studies Seminar series. Paper presented 29 July 1985
Keywords: Poverty. South Africa; Poverty. Government policy. South Africa; Poor. South Africa; South Africa. Economic conditions, 1961-1991; South Africa. Social conditions, 1961-1994